REDUCTION TRANSLATION TECHNIQUE IN THE MOVIE ENTITLED LITTLE WOMEN - Andina Fahru Hindra Sari; Christina Maya Iriana Sari (Universitas Katolik Widya Mandala Surabaya, 2024)
Movie subtitling has become a bridge in translation language for the international film industry. Subtitling is required by audiences who need information of any other language in some media, especially on audio-visual text. In translating, a movie script consists of language units that need an exact translation strategy. Movie subtitles are not more than two lines, to streamline the movie script on subtitled display, a reduction translation techniques strategy is used. This research has two aims analyzing the reduction technique by Molina and Albir (2002) and the translation accuracy in reducing subtitles in the movie by Nababan (2012). This study is descriptive qualitative research, the content analysis is used as a method to identify and analyze the reduction techniques in movies and the translation accuracy in reducing subtitles in the movie. The result findings are the language unit translated by deletion are 79 data (68.69%), concision 34 data (29.56%), and implicitation 2 data (1.73%). The most dominant technique is deletion. The total of accurate translations is 91 data (79.13%) then the total of less accurate and inaccurate translations is 19 data (16.52%) and 5 data (4.34%). The researcher finds that the reduction translation technique in Little Women movies results in accurate translation.